2017
DOI: 10.3389/fpubh.2017.00222
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resonance Frequency Breathing on Measures of Heart Rate Variability, Blood Pressure, and Mood

Abstract: Heart rate variability biofeedback (HRVB) significantly improves heart rate variability (HRV). Breathing at resonance frequency (RF, approximately 6 breaths/min) constitutes a key part of HRVB training and is hypothesized to be a pathway through which biofeedback improves HRV. No studies to date, however, have experimentally examined whether RF breathing impacts measures of HRV. The present study addressed this question by comparing three groups: the RF group breathed at their determined RF for 15 min; the RF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 26 publications
(45 reference statements)
9
94
3
3
Order By: Relevance
“…Furthermore, we used a breathing frequency of 0.1 Hz for all participants, but the frequency that produces maximal RSA (the so‐called resonance frequency) differs slightly between individuals. A recent study by Steffen et al () showed that breathing at resonance frequency produced a larger improvement in positive mood than breathing at a respiratory rate higher by one breath per minute. Therefore, future studies might determine the participants’ individual resonance frequencies and thus maximize RSA instead of using the same frequency for all participants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, we used a breathing frequency of 0.1 Hz for all participants, but the frequency that produces maximal RSA (the so‐called resonance frequency) differs slightly between individuals. A recent study by Steffen et al () showed that breathing at resonance frequency produced a larger improvement in positive mood than breathing at a respiratory rate higher by one breath per minute. Therefore, future studies might determine the participants’ individual resonance frequencies and thus maximize RSA instead of using the same frequency for all participants.…”
Section: Discussionmentioning
confidence: 98%
“…Van Diest et al () reported that participants had lower affective arousal after breathing at 0.1 Hz in comparison to 0.2 Hz. Recently, Steffen, Austin, DeBarros, and Brown () reported no effect on anxious arousal but increased positive mood. Thus, research has shown that breathing at 0.1 Hz may modulate affective state.…”
Section: Introductionmentioning
confidence: 97%
“…It is obvious that low-frequency breathing has caused the LF power to increase in YG, PBG than NBG. In a physiological perspective, it is well known that the increase in RSA would exert a favorable impact on pulmonary gas exchange by keeping tidal volume or the breathing frequency constant (Cysarz & Bussing, 2005;Hayano & Yasuma, 2003;Hirsch & Bishop, 1981;Steffen et al, 2017;Tripathi, 2004). Statistically significant increase in TINN, SDNN, and TSD2 of YG, PBG-3 cpm, and PBG-7 cpm as compared to NBG mark a higher variability in heart rate that could be expected for a healthy heart (Shaffer & Ginsberg, 2017).…”
Section: Breathing and Hrvmentioning
confidence: 99%
“…get influenced either in an inhibitory or excitatory way by behavioral reflexes of central nervous system (CNS) (Shea, 1996). The susceptibility of the cardiac autonomic controls to external rhythms has been studied by some researchers (Charnock & Manenica, 1978;Steffen et al, 2017). By minimizing or subduing other behavioral influences the self sustained neural pacemaker at the brain stem might have competed to favor a regular respiratory rhythm (Shea, 1996).…”
Section: Relationship Between Attention and Breathingmentioning
confidence: 99%
See 1 more Smart Citation